2017
DOI: 10.1080/02670836.2017.1288777
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and thermodynamic calculations of biodegradable Mg–2.2Zn–3.7Ce and Mg–Ca–2.2Zn–3.7Ce alloys

Abstract: In the present study, the effect of Ca (0.5–6 wt-%) content on the microstructure, phase formation, and mechanical properties and in vitro degradation behaviour of Mg–2.2Zn–3.7Ce alloys were investigated. Microstructural analysis and thermodynamic calculations also showed that Mg–2.2Zn–3.7Ce alloy contain α-Mg, Mg12Ce and CeMgZn2, while after adding 0.5 wt-% Ca to Mg–2.2Zn–3.7Ce alloy, IM1 (Ca3Mg xZn15− x) (4.6 ≤  x ≤ 12) phase was detected. Further addition of Ca to 6 wt-% resulted in forming Mg2Ca besides α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Likewise, it was suggested [20] that CNTs contain a great amount of cylindrical layers of graphite-like sp 2 -bonded cylindrical layers, where the intershell interactions are mainly van der Waals, that may effortlessly slide over each other, resulting in the reduction of the friction coefficient. In addition, by incorporation of CNTs, the porosities of the coating would be filled and the [41][42] CNTs could act as nano-lubricants which will effectively decrease the volume loss from abrasive wear. Taken together, incorporation of CNTs in the APS coating is beneficial for the enhancement of the tribological behaviour of APS ceramic coatings.…”
Section: Mechanical Properties Of the Uncoated And Aps-coated Samplesmentioning
confidence: 99%
“…Likewise, it was suggested [20] that CNTs contain a great amount of cylindrical layers of graphite-like sp 2 -bonded cylindrical layers, where the intershell interactions are mainly van der Waals, that may effortlessly slide over each other, resulting in the reduction of the friction coefficient. In addition, by incorporation of CNTs, the porosities of the coating would be filled and the [41][42] CNTs could act as nano-lubricants which will effectively decrease the volume loss from abrasive wear. Taken together, incorporation of CNTs in the APS coating is beneficial for the enhancement of the tribological behaviour of APS ceramic coatings.…”
Section: Mechanical Properties Of the Uncoated And Aps-coated Samplesmentioning
confidence: 99%
“…It was exhibited [10] that incorporation of antimony (Sb) might considerably enhance bonding of the deposited layer and the substrate. In this regard, it was reported that [11][12][13][14][15] cooling curve thermal analysis was employed as essential technique to determine phase formation and solidification path throughout the casting procedure. However, the phase identification and thermodynamic calculations of Zn-Al-Mg-xSb (x = 0, 0.1, 0.3 and 0.5 wt-%) coated steel wires has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%